Of corpse : death and humor in folklore and popular culture - Narváez, Peter (Utah State University Press, 2003)
"Laughter, contemporary theory suggests, is often aggressive in some manner and may be prompted by a sudden perception of incongruity combined with memories of past emotional experience. Given this importance of the past to our recognition of the comic, it follows that some "traditions" dispose us to ludic responses. The studies in this collection examine specific interactions of text (jokes, poetry, epitaphs, iconography, film drama) and social context (wakes, festivals, disasters) that shape and generate laughter. Uniquely, however, the essays here peruse a remarkable paradox--the convergence of death and humor"--Publisher's description